An introduction to Judaism - De Lange, N. R. M. (Nicholas Robert Michael), 1944- (Introduction to religion., 2000)
A full and lucid account of Judaism and the Jewish people, written for Jews and non-Jews alike - be they students, teachers, or general interested readers. Contains illustrative tables and maps, a full glossary, chronology, bibliography and index. This is a stimulating and comprehensive introduction to a major world culture.